Ocular Manifestations of Ebola Virus Disease: An Ophthalmologist's Guide to Prevent Infection and Panic - Vingolo, Enzo Maria (Biomed Res Int, 2015)
Ebola virus disease (EVD—formerly known as Ebola hemorrhagic fever) is a severe hemorrhagic fever caused by lipid-enveloped, nonsegmented, negative-stranded RNA viruses belonging to the genus Ebolavirus. Case fatality rates may reach up to 76% of infected individuals, making this infection a deadly health problem in the sub-Saharan population. At the moment, there are still no indications on ophthalmological clinical signs and security suggestions for healthcare professionals (doctors and nurses or cooperative persons). This paper provides a short but complete guide to reduce infection risks.